Revealing Charge‐ and Temperature‐Dependent Movement Dynamics and Mechanism of Individual Molecular Machines. Issue 12 (3rd September 2019) - Zhou, Ce; Li, Xingxing; Masai, Hiroshi; Liu, Zihao; Lin, Yuanwei; Tamaki, Takashi; Terao, Jun; Yang, Jinlong; Guo, Xuefeng
Abstract: Single‐molecule detection is able to reveal rich spatial/temporal information and elucidate intrinsic mechanisms of inter or intramolecular interactions that are not accessible in ensemble experiments, which is of fundamental importance to solve the key issues in physical, chemical, and biological sciences. Here, a robust, label‐free single‐molecule electrical approach capable of directly exploring the detailed dynamic process of stochastic movement of alkyl chains bearing different charges through a macrocycle in a molecular machine at the single‐event level is represented by using stable graphene–molecule–graphene single‐molecule junctions (GMG‐SMJs). These junctions are built by covalently sandwiching a pseudorotaxane featuring a permethylated α‐cyclodextrin between nanogapped graphene electrodes. In situ long‐term single‐molecule electrical measurements unambiguously show reproducible large‐amplitude multiple‐level fluctuations that are highly dependent on charge and temperature. Both theoretical simulations and experimental data prove that this observation originates from random motions of alkyl chains along the axle within a time scale of a few milliseconds. Observation of transient changes in current signals by gating effects allows direct real‐time monitoring of the submolecular translational process. These investigations conceptualize the capability of GMG‐SMJs to probe fast single‐molecule chemical reactions or behaviors. Abstract : Charge‐ and temperature‐dependent movement dynamics and mechanism of molecular machines are revealed at the single‐event level when covalently sandwiched between nanogapped graphene electrodes to form stable graphene–molecule–graphene single‐molecule junctions. These investigations conceptualize the capability of single‐molecule electronic devices to probe fast single‐molecule physics, potentially revolutionizing the current technique to visualize single‐molecule chemical reactions or behaviors.